Chemical Profile of proximate composition L. (King and Robinson) Leaves - Ngozi, Igboh M.; Jude, Ikewuchi C.; Catherine, C. (Pakistan Journal of Nutrition, 2009)
The proximate, amino acid and phytochemical composition of Chromolaena odorata was investigated. A high total carbohydrate (20.58% WW and 50.82% DW), crude fibre (10.76% WW and 26.57% DW) and protein (6.56% WW and 16.20% DW) content was observed. The protein is rich in the essential amino acids (with histidine and phenylalanine being very high) and has a protein score of 88.24% with methionine as the limiting amino acid. The phytochemical screening revealed the presence of alkaloids, cyanogenic glycosides, flavonoids (aurone, chalcone, flavone and flavonol), phytates saponins and tannins. The anti-nutrients composition includes cyanogenic glycosides (0.05% WW and 0.13% DW), phytates (0.22% WW and 0.54% DW), saponins (0.80% WW and 1.98% DW) and tannins (0.15% WW and 0.37% DW). Our result suggests that C. odorata is a source of high quality protein which could serve as a potential source of protein supplement.